Uso de las herramientas de Inteligencia artificial en la Carrera de Pedagogía de las Ciencias Experimentales: Informática - Castro Estacio, Edison Oswaldo (2025)
This research analyzes the usage levels of Artificial Intelligence (AI) tools among students in the Computer Science Education program at the Universidad Nacional de Chimborazo. The study adopted a quantitative approach with descriptive scope and non-experimental cross-sectional design, applying an adapted structured questionnaire to a sample of 93 students from a population of 163. Results reveal significant but unequal adoption of AI tools. ChatGPT and Canva emerge as the most widely used platforms, with adoption rates of 81.72% and 68.82% respectively, while tools such as Stability AI, DALL-E2, and Synthesia show non-usage rates exceeding 75%. The analysis demonstrates that 90% of students consider ChatGPT useful or very useful, and the main perceived advantages include speed in content generation (63.4%) and ease in addressing complex topics (63.8%). The research evidences a significant gap in digital literacy regarding various AI technologies, with usage concentrated on a limited number of platforms. Students show substantial integration of these tools into their academic routines, with usage patterns ranging from 30 minutes to more than 3 hours daily. The study concludes that there is considerable potential for AI integration in higher education, but emphasizes the need for broader training programs and policies that promote responsible and ethical use of these technologies.